PENGARUH GAYA KEPEMIMPINAN DAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PENGELOLAAN PENGADUAN PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) - Frency, Jodi; Rachbini, Widarto; Salim, Fachrudin (SEKOLAH PASCASARJANA PRESS, 2022)
This 2021 research is entitled The Effect of Leadership Style and Information Technology on Employee Performance with Motivation as an Intervening Variable in the Implementation of the Non-Cash Food Aid Complaint Management Program (BPNT). The purpose of this study is to analyze whether there is a significant influence between Leadership Style and Information Technology on Employee Performance in the Implementation of the Non-Cash Food Assistance Complaint Management Program (BPNT) based on the Special Guidelines for Food Social Assistance Complaint Management, with motivation as an intervening variable. The success of the Non-Cash Food Assistance Program (BPNT) is largely determined by six aspects (6T), namely staying on target, being on time, in the right quantity, right at the price, right in quality and right in administration. These six aspects are still a problem in the distribution of the Non-Cash Food Assistance Program (BPNT). The Complaint Management System (SPP) is expected to provide access for community participation in order to support the success of the program and also as a means of supporting the Directorate General of Development Development in carrying out its duties as coordinator of the central level SPP. The research method used is ExPost Facto Causality Research, with this type of research based on a time approach using a Cross Sectional approach. Data management in this study will use PLS 3.2.6 Smart Software Structural Equation Modeling (SEM) Variance Based SEM or Partial Least Square (PLS) is a method used to cover the weaknesses contained in the regression method. While the sample technique used is Non-Probability Sample / Purposive Sampling which uses a total sample of 40 people. In the whole of this study, in the whole of this study, the biggest influence on the t test is on the effect of Information Technology on Motivation (t count of 15,704 is greater than t table of 1.96), Information Technology has a positive and significant effect on motivation. Then, Leadership Style has a positive and significant effect on Employee Performance, because based on statistical parameters it shows that the t count of 2.079 is greater than the t table of 1.96.